Is any landmark reliable in vertebral enumeration? A study of 3.0-Tesla lumbar MRI comparing skeletal, neural, and vascular markers - TÜRELİ, DERYA; BALTACIOĞLU, FEYYAZ; EKİNCİ, GAZANFER (ELSEVIER SCIENCE INC, 2014)
Purpose: This study aimed to determine the reliability of the iliolumbar ligament (ILL), 12th costa, aortic bifurcation (AB), Tight renal artery (RRA), and conus medullaris (CM) for numbering of vertebral segments. Subjects and methods: Five hundred five patients underwent routine lumbar MRI examinations including a cervicothoracic sagittal scout and T1 and T2-weighted sagittal and axial turbo spin echo images. Images were evaluated by two radiologists separately. Results: The identifiability of ILL and 12th costa were 85.7% and 48.1%. AB, RRA, and CM were located more caudally in lumbarized S1 and more cranially in sacralized L5 cases. Conclusion: Landmarks suggested by previous studies are not reliable alternatives to cervicothoracic scout images due to wide ranges of distribution and inconsistencies in identification. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Magnetic resonance imaging; Iliolumbar ligament; Lumbosacral transitional vertebrae; Aortic bifurcation; Renal artery; ILIOLUMBAR LIGAMENT; AORTIC BIFURCATION; CONUS MEDULLARIS; SPINE; CLASSIFICATION; SEGMENTS